Online Recommendation System - The Potential And Possibilities Of World -Of- Mouth On The Internet - T., Ramayah; Yeap, Ai Leen; Ignatius, Joshua (Universiti Sains Malaysia, 2011)
In recent years, the unprecedented growth in web technology has enabled web users to attain a more active role in communicating via the Internet. Not only can web users obtain information through the Internet, they can now also post information online. As a result, consumers' electronic word-of-mouth (eWOM) communication can be easily disseminated through Web 2.0 applications such as online discussion forums, electronic bulletin board systems, newsgroups, blogs, review sites, and social networking sites.